Tiny tough - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory., 2019)
"Dory's sure that her big sister's friendship troubles have to do with pirates, but she'll have to navigate those rocky waters without her imaginary first mate Mary, who's found an exciting new pal of her own"--